Disparities in Women's Prison Sentences: Exploring the Nexus Between Motherhood, Drug Offense, and Sentence Length. (October 2019) - Cho, Ahram; Tasca, Melinda
Drawing upon focal concerns and familial paternalism frameworks, we explore the effects of motherhood, various maternal indicators, and type of offense on prison sentences using official and self-report data on 419 incarcerated women in the United States. Results revealed that drug offenders were sentenced more leniently than other offenders, whereas mothers were not sentenced differently from women without children. Mothers who lived with their children received shorter prison terms than mothers who were absent prior to arrest. This study fills gaps in knowledge on discretion in punishment in light of growing rates of female imprisonment.